2017
DOI: 10.5301/jva.5000632
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing dialysis arteriovenous graft survival

Abstract: Coronary artery disease negatively influences the cumulative patency of vascular access. Higher serum cholesterol levels are associated with lower AVG failure risk over a 1000-day period, which probably corresponds to the worse disease status of the patients with lower cholesterol values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…revealed that compared to nonsmoking patients, smoking patients had lower AVG thrombosis rates. 38,39 Therefore, our result indicating a protective effect of smoking on AVG patency is not unique.…”
Section: Discussionmentioning
confidence: 65%
“…revealed that compared to nonsmoking patients, smoking patients had lower AVG thrombosis rates. 38,39 Therefore, our result indicating a protective effect of smoking on AVG patency is not unique.…”
Section: Discussionmentioning
confidence: 65%
“…Patients may develop steal in case of ipsilateral AVF and left internal mammary coronary artery bypass grafting with worsening of angina pectoris (10). Interestingly, the presence of coronary artery disease is associated with shorter arteriovenous graft lifespan (11).…”
Section: Arterial Diseasementioning
confidence: 99%
“…1,6) Many factors that may affect the patency of AVG have been proposed, such as medication (clopidogrel, aspirin, and dipyridamole), coronary disease, serum cholesterol level, location, and configuration. 7,8) In our study, no improvement of patency was shown among patients on antiplatelet or anticoagulant therapy ( Table 1 ). In many studies, the correlation between the location of AVG and the patency has been evaluated, and these results may imply that the more proximal the anastomosis the larger the vessel and better patency.…”
Section: Discussionmentioning
confidence: 47%